SKRINING GULA DARAH SEWAKTU (GDS) DAN KADAR ASAM URAT PADA MASYARAKAT MENDALO DARAT DI POLIKLINIK PINANG MASAK UNIVERSITAS JAMBI - Elfiani; Ahmad Syauqy; Erny Kusdiyah (Universitas Jambi, 2020)
ABSTRACT Diabetes and Gout Arthritis are diseases where the number of sufferers has increased quite high every year. Both diseases are very much influenced by a person's diet and lifestyle. The low level of public interest in doing regular screening of blood sugar and blood uric acid levels as indicators to determine the incidence of diabetes and gout arthritis are one of the factors in the increasing number of these diseases from year to year. The reasons for this reluctance were varied, starting from the aspect of cost, affordability to the location of the inspection, limited infrastructure and time aspects. For this reason, community service activities are necessary to facilitate this. This activity was carried out on September 1, 2020, in the form of checking blood sugar and uric acid levels in the Mendalo Darat community and UNJA staff / lecturers at the Pinang Masak Polyclinic, Jambi University. This activity uses the easy tauch digital tool and after that, participants can consult with the health workers we have prepared and also receive treatment if their blood sugar and uric acid levels exceed normal limits. The number of participants who took part in this examination were 104 people from the community, employees and lecturers in the UNJA environment. This activity is carried out by implementing strict health protocols related to the prevention of Covid-19 transmission. From the results of blood sugar tests, 9% were in the abnormal category and 43% were in the abnormal category for uric acid tests. Key words: blood sugar levels, uric acid levels